Action Plan for Service Quality of Science and Technology Area Based on Partners and Tenants Perception - Dyah Zahra Wati; Eko Pujianto; Fakhrina Fahma (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2023)
Abstract— Solo Technopark as one of Science and Technology Area and also called STP develops economic potential and investment attractiveness in Surakarta through the presence of partners and tenants with offices in the area. Partners and tenants have the potential to become Surakarta’s revenue boosters through a lease and grant mechanism. STP has tried to maintain the satisfaction of partners and tenants, but there are still complaints from partners and tenants. It is necessary to improve the quality of service so that partners and tenants trust and stay at STP. This study uses Importance Performance Analysis (IPA) and Quality Function Deployment (QFD) methods to overcome these problems. The entire population became respondents in this study, there are 15 partners and tenants companies with offices at STP and were determined through purposive sampling. Data were collected using the questionnaire and interview methods for the measurement period January-March 2023. The novelty of this research is combination of five dimensions of SERVQUAL, namely tangible, reliability, responsiveness, assurance, empathy with technology and security factors. Through gap analysis, as many as 84% of 31 valid and reliable service quality attributes were stated by partners and tenants to be dissatisfied. The research results is eight priority service attributes to develop service quality improvement proposals. The four designs plan for improving service quality are investing in the latest technology and information, providing skilled and trained technical teams, recruiting social media specialists, and more active and creative management. Implementation of these action plan will increase partner and tenant satisfaction, but there are time and cost adjustments that need attention. This research also provides an understanding of attributes of science park services, provides guidance and recommendations in developing strategies or policies in the field of science park for managers and the government.